2012
DOI: 10.4103/0019-5154.103067
|View full text |Cite
|
Sign up to set email alerts
|

Childhood vitiligo: Treatment paradigms

Abstract: Childhood vitiligo differs from the adults by showing a higher incidence in females, segmental vitiligo being more common and less frequent association with other systemic autoimmune and endocrine disorders. Childhood vitiligo is often associated with a marked psychosocial and long lasting effect on the self-esteem of the affected children and their parents, hence an adequate treatment is very essential. Treatment of vitiligo is indeed a tough challenge for the dermatologists’ more so in the background of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…However, vitiligoʼs impact goes beyond skin discoloration, as this condition can affect patientsʼ emotional health, leading to lower self-esteem and a psychosocial impact on children [3]. Studies using quality of life psychiatric morbidity questionnaires have shown a prevalence of psychiatric morbidity, including depressive episodes, adjustment disorders, and anxiety in 25 % of patients with vitiligo [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, vitiligoʼs impact goes beyond skin discoloration, as this condition can affect patientsʼ emotional health, leading to lower self-esteem and a psychosocial impact on children [3]. Studies using quality of life psychiatric morbidity questionnaires have shown a prevalence of psychiatric morbidity, including depressive episodes, adjustment disorders, and anxiety in 25 % of patients with vitiligo [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…NBUVB therapy is now a more or less established and recommended phototherapy for generalized vitiligo, pregnant women, and children because of the high safety profile. [3][4][5] Determination of MEDs is essential for rational treatment with UV light. Serish and Srinivas reported that the mean MED for NBUVB was 300 mJ/cm 2 for the Indian adults skin.…”
Section: Discussionmentioning
confidence: 99%
“…NBUVB also has been increasingly tested in the pediatric population as a therapy for diseases, including vitiligo and atopic dermatitis. [1][2][3][4][5] In 1997, Westerhof and Nieuweboer-Krobotova [6] were the first to study the effect of NBUVB in vitiligo. In 2000, Njoo et al [7] and 2005, Kanwar and Dogra [8] ABSTRACT Background: Management of vitiligo in children is difficult as therapeutic options are restricted when compared to that in adult patients.…”
mentioning
confidence: 99%
“…tachyphylaxis, suppression of hypothalamic-pituitary-adrenal axis, Cushing’s syndrome and growth retardation). In detail, the use of TCs on vitiligo patches of the face should be avoided or limited in time because of the higher risk of topical side effects, including glaucoma [ 6 ][ 7 ].…”
Section: Topical Treatmentsmentioning
confidence: 99%